Outcomes associated with translocation of mule deer (Odocoileus hemionus): Influence of age, release timing, and year on survival - Smedley, David C.; McMillan, Brock R.; Hersey, Kent R.; Shannon, Justin M.; Larsen, Randy T. (Frontiers in Ecology and Evolution, 2023)
Translocation of large mammals has become common practice for wildlife managers charged with conservation of animals on increasingly modified landscapes. Translocations of ungulates have occurred around the world with varying outcomes. Although translocations have been used to manage mule deer (Odocoileus hemionus) in western North America, only recently have the outcomes associated with this management practice been documented. Our objective was to evaluate survival of translocated mule deer in comparison to resident mule deer over multiple years following release and provide information useful in judging the relative value of translocation as a conservation strategy for this species. In January and March 2013, the Utah Division of Wildlife Resources (UDWR) captured and translocated 102 mule deer from winter range near Parowan, Utah to winter range near Holden, Utah (approximately 145 kilometers north of capture location). We fitted each deer with a radio transmitter (n = 102 total: 21 GPS collars, 81 VHF collars) prior to release. We also captured and marked a total of 70 resident deer (9 GPS collars, 61 VHF collars) to serve as a reference group. Annual survival was greater for resident deer (0.83; 95% CI = 0.72 – 0.90) than translocated deer (January release 0.51; 95% CI = 0.40 – 0.63, March release 0.53; 95% CI = 0.40 – 0.66) during the first year after translocation. We found no difference in survival for translocated deer released in January and March during the first year following release. During the second year following release, however, survival of translocated animals (0.85; 95% CI = 0.71 – 0.93) was not different from that of resident deer (0.80; 95% CI = 0.69 – 0.88). Additionally, age strongly influenced the survival of translocated deer; young deer (e.g., 1.5 year olds) were more than twice as likely as old deer (e.g., 7.5 year olds) to survive the year following translocation. These data highlight the need to monitor translocated animals for multiple years following release and suggest that wildlife managers should expect to see higher survival rates during the second year following translocation and higher survival rates in younger deer compared to older deer.